A comparative study of early grade writing assessment in 2nd grade elementary students in urban, suburban, and rural areas in Pekalongan - Adiyatma Nur Zain Purohita; Moh. Farizqo Irvan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study provides evidence of early literacy gaps as measured by EGWA in the Indonesian context. This study aims to compare the early writing skills of second-grade elementary students in urban, suburban, and rural areas. The study used a quantitative, comparative research design and was conducted in three elementary schools in Pekalongan. The subjects were second-grade students selected using simple random sampling. Data collection was carried out using an early writing skills test administered with the standardized and reliable Early Grade Writing Assessment (EGWA) instrument. The data obtained were analyzed statistically to determine differences in early writing skills across regions. The research results indicate a significant difference in the average between urban and rural areas. The averages are 89.30 for SDN 01 Pekuncen (urban area), 88.03 for SDN 03 Sragi (suburban area), and 80.55 for SDN 03 Tengeng Wetan (rural area). The analysis results using the Kruskal–Wallis test indicate significant differences in early literacy scores between children in urban and rural areas, providing initial empirical evidence of the literacy gap measured by EGWA in Indonesia